Curcumin (CurcuWIN™) Improves Antioxidant Capacity and Reduces Inflammation Following Downhill Running-Induced Muscle Damage - Juturu, Vijaya; Şahin, Kazım; Pala, Ragip; Tuzcu, Mehmet; Şahin, Nurhan; Ozdemir, Oguzhan; Deshpande, Jayant (Federation Amer Soc Exp Biol, 2015)
[Abstract Not Available]
Experimental Biology Meeting -- MAR 28-APR 01, 2015 -- Boston, MA